2001
DOI: 10.1097/00001813-200102000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolyzable hydrophobic taxanes: synthesis and anti-cancer activities

Abstract: A series of taxane prodrugs with 2-bromoacyl chains attached at the 2'-position of the paclitaxel side chain, varying from six, eight, 12, 14 to 16 carbons in length, were synthesized, characterized and evaluated against human breast MCF-7 cancer cell line for their growth inhibitory (GI50) activities. The GI50 is the drug concentration required to inhibit cell growth by 50%. For comparison, hydrophobic taxanes varying in acyl chain lengths from six to 16 carbons were also synthesized and compared for their G0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
38
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 8 publications
6
38
0
Order By: Relevance
“…Many studies have reported the reduction of PX or DX activity by conjugating fatty acid chains to 2′-OH. 21,23,24 This study is consistent with previous reports that in general, all three DX-lipid conjugates were less potent than DX against DU-145 cells, and increasing the lipid chain length decreased the cell growth inhibitory activity in vitro. It has been previously demonstrated that esterification at 2′-OH or 7-OH abolished the microtubule binding affinity of the conjugates but not the total toxicity.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Many studies have reported the reduction of PX or DX activity by conjugating fatty acid chains to 2′-OH. 21,23,24 This study is consistent with previous reports that in general, all three DX-lipid conjugates were less potent than DX against DU-145 cells, and increasing the lipid chain length decreased the cell growth inhibitory activity in vitro. It has been previously demonstrated that esterification at 2′-OH or 7-OH abolished the microtubule binding affinity of the conjugates but not the total toxicity.…”
supporting
confidence: 91%
“…21 It has been previously reported that the conjugation of fatty acids to DX and PX occurs preferentially on 2′-OH. 21,23,24 By controlling the molar ratio of the fatty acid chloride to DX carefully, 2′-mono substituted DX conjugates were obtained with minimal formation of 2′,7-di substituted byproducts and unreacted DX. In the case of C22-DX, only the 2′-OH ester derivative was obtained after washing with 5% HCl and brine as determined by thin layer chromatography and nuclear magnetic resonance, without further chromatography required.…”
Section: Synthesis and Characterization Of DX Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Briefly, PX was conjugated with 2-bromohexadecanoic acid via a one-step esterification reaction with DMAP (SigmaAldrich Co.) as the catalyst. The product was purified by preparative thin layer chromatography.…”
Section: Optimization and Characterization Of Br-c16-px Npsmentioning
confidence: 99%
“…Previously Ali et al synthesized a series of lipophilic PX conjugates bearing 6, 8, 12, 14, or 16-carbon chains at the 2′-position. 9 The PX conjugate with a long 16-carbon chain exhibited decreased cytotoxicity compared to conjugates with shorter chain lengths, but was therapeutically more efficacious when loaded into liposomes for the treatment of mouse ovarian cancer. Moreover, the incorporation of an electron-withdrawing bromine (Br) atom was evaluated in the PX conjugates.…”
Section: Introductionmentioning
confidence: 96%